Effect of Rock Composition on Appearance of Garnet in Anorthosite–Charnockite Suites - Martignole, J.; Schrijver, K. (Canadian Journal of Earth Sciences, 1973)
Fe 2+ /Mg and normative An/Ab ratios of 55 rocks of the Adirondack anorthosite–charnockite suite subdivide the compositional field in two domains; one without garnet (at low ratios) and one commonly with garnet (at high ratios). A similar subdivision is shown by 27 rocks of the Morin Complex. On the other hand, this subdivision is not valid for small anorthosite–charnockite complexes in the southern, Canadian, part of the Grenville Province, nor for the huge Nain (Labrador) anorthosite–adamellite massif.These different relations can be explained by: (1) formation of garnet during cooling under high confining pressure in the southern part of the Grenville Province, the size of the anorthosite–charnockite body determining the rate of cooling and (2) cooling of the Nain massif under lower confining pressure.